The Effect of Triangle Family Therapy on the Stress of Families Caring for Schizophrenic Clients at Especially Mental Hospital Prof. Dr. Muhammad Ildrem - Sri Adriana A Siahaan; Siti Saidah Nasution; Wardiyah Daulay (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The family's understanding of fulfilling the patient's needs and patient behaviour that is difficult to understand results in problems in the relationship between the family and the patient, which can ultimately cause stress in the family. This stressful condition can affect the attitudes, behaviour and interpersonal relationships of family members who care for scozyprenia patients. This study aims to examine the effect of triangle family therapy on family stress caring for schizophrenic clients at the Special Prof.Dr.M. Ildrem Mental Hospital. The research method uses a quasi-experimental method with a pretest and post-test non-equivalent control group design. The sampling technique is a non-probability sampling technique, namely the purposive sampling method. The population in this study were all families who had family members who have schizophrenia. The respondents of this study were families who had family members who have schizophrenia in the Technical Implementing Service Unit (UPTD) Special Outpatient Room at the Mental Hospital Prof. Dr. Muhammad Ildrem Medan, consisting of 30 intervention group respondents and 30 control group respondents. The fatigue measurement instrument uses the Perceived Stress Questionnaire (PSQ). Data were analyzed using independent t-tests and paired t-tests. The research results found that triangle family therapy significantly reduced family stress caring for schizophrenia patients with a p-value <0.05. The conclusion is that triangle family therapy is effective in reducing family stress in caring for schizophrenia patients and is recommended as a nursing intervention to reduce family stress caring for schizophrenia patients.Keywords: Schizophrenia, Stress, Triangle family therapy